A Lipid-Anchored NAC Transcription Factor Is Translocated into the Nucleus and Activates Glyoxalase I Expression during Drought Stress. Issue 7 (6th July 2017) - Duan, Mei; Zhang, Rongxue; Zhu, Fugui; Zhang, Zhenqian; Gou, Lanming; Wen, Jiangqi; Dong, Jiangli; Wang, Tao
Abstract : Under drought stress, lipid-anchored MfNACsa translocates to the nucleus by thioesterase MtAPT1-dependent de- S -palmitoylation, regulating GlyI gene expression and GSH/GSSG ratio. Abstract: The plant-specific NAC (NAM, ATAF1/2, and CUC2) transcription factors (TFs) play a vital role in the response to drought stress. Here, we report a lipid-anchored NACsa TF in Medicago falcata . MfNACsa is an essential regulator of plant tolerance to drought stress, resulting in the differential expression of genes involved in oxidation reduction and lipid transport and localization. MfNACsa is associated with membranes under unstressed conditions and, more specifically, is targeted to the plasma membrane through S -palmitoylation. However, a Cys26 -to-Ser mutation or inhibition of S -palmitoylation results in MfNACsa retention in the endoplasmic reticulum/Golgi. Under drought stress, MfNACsa translocates to the nucleus through de- S -palmitoylation mediated by the thioesterase MtAPT1, as coexpression of APT1 results in the nuclear translocation of MfNACsa, whereas mutation of the catalytic site of APT1 results in colocalization with MfNACsa and membrane retention of MfNACsa. Specifically, the nuclear MfNACsa binds the glyoxalase I ( MtGlyl ) promoter under drought stress, resulting in drought tolerance by maintaining the glutathione pool in a reduced state, and the process is dependent on the APT1-NACsa regulatory module. Our findings reveal a novel mechanism for the nuclear translocation of an S -palmitoylated NAC in response to stress.